2018
DOI: 10.3389/fimmu.2018.02396
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphoid Cells in the Maternal and Fetal Compartments

Abstract: Pregnancy success is orchestrated by the complex balance between the maternal and fetal immune systems. Herein, we summarize the potential role of innate lymphoid cells (ILCs) in the maternal and fetal compartments. We reviewed published literature describing different ILC subsets [ILC1s, ILC2s, ILC3s, and lymphoid tissue inducer (LTi) cells] in the uterus, decidua, fetal tissues [liver, secondary lymphoid organs (SLO), intestine, and lung] and amniotic cavity. ILC1s, ILC2s, and ILC3s are present in the murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 167 publications
(288 reference statements)
1
65
0
Order By: Relevance
“…On this basis, ILC have been described as "innate counterparts" of T cells (151). Their abundance at the maternal-fetal interface suggests pivotal roles in both innate immune defense and normal placental development (152). Table 2 summarizes the classification and functions of decidual ILC: Given the recent discovery of ILC, data on their antiviral properties are still accumulating.…”
Section: Innate Lymphoid Cellsmentioning
confidence: 99%
“…On this basis, ILC have been described as "innate counterparts" of T cells (151). Their abundance at the maternal-fetal interface suggests pivotal roles in both innate immune defense and normal placental development (152). Table 2 summarizes the classification and functions of decidual ILC: Given the recent discovery of ILC, data on their antiviral properties are still accumulating.…”
Section: Innate Lymphoid Cellsmentioning
confidence: 99%
“…Amniotic fluid contains a diverse array of innate and adaptive immune cells that vary as normal gestation progresses [49]. Specifically, neutrophils, monocytes/macrophages, T cells, innate lymphoid cells, natural killer (NK) cells, and B cells are present in the amniotic cavity of women with a normal pregnancy [49][50][51]. These cellular immune responses are augmented in women with pregnancy complications such as preterm labor with intact membranes [52], clinical chorioamnionitis at term [53], and preterm clinical chorioamnionitis [54].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most studied causes of pathological inflammation leading to preterm labor have been (a) intra‐amniotic infection/inflammation resulting from microbial invasion of the amniotic cavity and (b) intra‐amniotic inflammation without detectable microorganisms (ie, sterile intra‐amniotic inflammation) identified by using both molecular and conventional microbiological techniques, proposed to be due to endogenous danger signals, or alarmins . Most research concerning inflammation‐induced preterm labor has therefore focused on the innate limb of immunity . Yet, several studies reported strong evidence that T cells, the primary cellular component of the adaptive immune system, are present at the maternal‐fetal interface .…”
Section: Introductionmentioning
confidence: 99%